2022
DOI: 10.1109/tem.2019.2950694
|View full text |Cite
|
Sign up to set email alerts
|

Multiagent Optimization Approach to Supply Network Configuration Problems With Varied Product-Market Profiles

Abstract: This paper demonstrates the application of a novel multi-agent modelling approach to support supply network configuration (SNC) decisions towards addressing several challenges reported in the literature. These challenges include: enhancing supply network (SN)-level performance in alignment with the goals of individual SN entities; addressing the issue of limited information sharing between SN entities; and sustaining competitiveness of SNs in dynamic business environments. To this end, a multi-stage, multi-ech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…Methods such as SD, ABM are able to simulate the intangible aspects of the SCM effectively, including interactions among different SC stages, learning over time for SC partners involved, and continuous feedback on key decisions in the presence of limited information. However, studies employing simulation modeling (e.g., ABM, SD) in the area have been few and far between, as reported in the recent study by Dharmapriya, Kiridena and Shukla (2019) . In fact, there are even less studies reported on modeling consumer behaviors in the SC using simulation modeling ( Taghikhah et al, 2019 ).…”
Section: Behavioral Modeling and Hybrid Simulationmentioning
confidence: 99%
“…Methods such as SD, ABM are able to simulate the intangible aspects of the SCM effectively, including interactions among different SC stages, learning over time for SC partners involved, and continuous feedback on key decisions in the presence of limited information. However, studies employing simulation modeling (e.g., ABM, SD) in the area have been few and far between, as reported in the recent study by Dharmapriya, Kiridena and Shukla (2019) . In fact, there are even less studies reported on modeling consumer behaviors in the SC using simulation modeling ( Taghikhah et al, 2019 ).…”
Section: Behavioral Modeling and Hybrid Simulationmentioning
confidence: 99%
“…These three technology-oriented drivers of supply chains can transform SCM from traditional to digitalized by integrating ecosystems that possess transparent interfaces. It has been observed that through a digitalized SCM system, firms can improve their customer and supplier management systems along with their supply chain agility and responsiveness [43] helpful to corelate demand and supply. Studies demonstrate that supply chain agility will help firms to have a flexible and effective supply chain system for their products [44,45].…”
Section: Literature Reviewmentioning
confidence: 99%
“…It means that after a product is put into the market, it is welcomed by users, and through market analysis, the enterprise responds quickly and makes a variant design on the basis of the original product [5].…”
Section: Configuration Management Of Enterprise Information Productsmentioning
confidence: 99%